Plan estratégico para la empresa Redingel Ltda. (2017)
The present work refers to the contextualization of the sector in which Redingel operates, where the behavior of the industry and the market is described. A bibliographic review of the most influential statistics in the aforementioned sector was carried out, the trajectory, main activity, current source of business, strategies implemented up to 2016 and organizational structure were presented in detail; In addition, a strategic diagnosis was made using managerial tools such as the DOFA, competitive profile and EFE and EFI matrices. At the end, the most suitable improvement strategies are proposed and coherent with the results obtained.